User attitude, organizational learning and dynamic capability in government-to-business success - Kassim, Erne Suzila; Hussin, Husnayati (2010)

(untitled)
A large number of studies has been conducted in an attempt to evaluate the government-to-business (G2B) success and investigate the usage determinants. However, there seems to be lack of research that assess the success criteria and look into the usage factors of user attitude, organizational learning and dynamic capability. Therefore, using a survey, we attempt to investigate the matter. Findings of the study suggest user attitude, organizational learning and dynamic capability have significant relationships with G2B system usage, while the usage have positive impacts towards the G2B success measured as process efficiency, information quality and satisfaction. Keywords - Government-to-business, system success, user attitude, organizational learning, dynamic capability